Oxidative Stress in Skeletal Muscle - Giorgio Fanò-Illic; Stefania Fulle (MDPI AG, 2022)
The accumulation of ROS, mainly due to increased mitochondrial production and/or decreased scavenger systems, is often associated with the term oxidative stress, used to define a condition judged to be problematic for muscle cells [...]